2004
DOI: 10.1111/j.1444-2906.2004.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion cooking temperature on the microstructure of extruded pellets

Abstract: The microstructure of extruded pellets (EP) for fish under various extrusion cooking temperatures was studied by using a twin-shaft extruder. As the extrusion cooking temperature increased, the expansion rate increased and the bulk density of EP decreased. The liquefaction of the material started because of the increase in inner material temperature, the decrease in inner material pressure, and the decrease in main motor amperage. Thus, the microstructure of EP changed depending on the extrusion cooking condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
3
7
0
1
Order By: Relevance
“…(). Similar effect of extrusion cooking temperature on the microstructure of extruded pellets has also been reported by Yoshitomi ().…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…(). Similar effect of extrusion cooking temperature on the microstructure of extruded pellets has also been reported by Yoshitomi ().…”
Section: Resultssupporting
confidence: 86%
“…An outgrowth‐like microstructure that is seen surrounded with thin cellular wall can be visualized at 140C resulting in the formation of large‐sized fibers, and the presence of big vacuole was observed with fractures because of the increase in temperature. Similarly, appearance of vacuole in microstructure with increase in extrusion temperature has been reported by Yoshitomi (). Increase in porosity or spongy texture with increase in temperature has also been reported by Cummings et al .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Algunos autores como Draganovic et al (2011) que han trabajado con esta clase de dietas observaron que la capacidad de absorción de aceite se afectaba por la porosidad del producto, con un rango de absorción entre 27.9 y 63.3% teniendo una correlación positiva con la humedad en el pellet y el contenido de gluten de trigo. La expansión de los pellets tiene gran importancia en la capacidad de absorción de aceite, aunque debe tenerse en cuenta que una expansión demasiado alta podría generar pellets de baja durabilidad, por esta razón el radio de expansión debe ser optimizado (Yoshitomi, 2004;Sørensen et al, 2011).…”
Section: Densidad Aparente (Da)unclassified
“…WHC of deboned meat-SPI blends after extrusion was obtained at 150℃ (Megard et al, 1985). Yoshitomi (2004), who investigated the extrusion of fish meal-wheat flour-defatted soybean meal blends in a twin-shaft extruder, found that temperature of approximately 155℃ maximized WHC. This phenomenon might result from an optimal equilibrium between protein unfolding and aggregation which would occur at around 150℃, resulting in a firm network (Megard et al, 1985).…”
Section: Water-holding Capacity (Whc)mentioning
confidence: 99%